(untitled) (Journal on studies and research of academic knowledge, 2024)
Yerba mate is a native plant of Paraguay, it stands out for being part of the country’s culture. Currently its production is affected by the deterioration of the soils, being thus a necessity to make better management and a correct fertilization to satisfy the demand. The research aimed to evaluate the effect of chemical fertilization and agricultural gypsum on the production of Yerba mate, year one. The experiment was carried out in San Alberto, Alto Parana, in a crop of 4 years of age (first year of harvest) in association with plants of paradise, in design of blocks completely random with 3 treatments T1: (Without chemical fertilization); T2: Chemical fertilization (60-40-60 kg.ha-1 of N, P2O5, K2O) and T3: Chemical fertilization with application of agricultural gypsum (60-40-60 kg.ha-1 of N, P2O5, K2O 2 t.ha-1 of agricultural gypsum) and 19 repetitions, totaling 57 experimental units. Commercial, non-commercial and total yields were determined. Analysis of variance was performed and the means were compared with the 5% Tukey test. There was no significant difference between treatments, production of the commercial part (T1:937 kg.ha-1, T2:972 kg.ha-1 and T3: 1278 kg.ha-1), non-commercial (T1:102 kg.ha-1, T2:157 kg.ha-1 and T3: 138 kg.ha-1) and total (T1:1039 kg.ha-1, T2:1129 kg.ha-1 and T3: 1415 kg.ha-1) were not influenced by the application of chemical fertilizers or the amendment.